2016
DOI: 10.1126/science.aaf0972
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 therapy with monoclonal antibody 3BNC117 elicits host immune responses against HIV-1

Abstract: 3BNC117 is a broad and potent anti-HIV-1 neutralizing antibody that targets the CD4 binding site on the viral envelope spike. When administered passively, this antibody can prevent infection in animal models and suppress viremia in HIV-1-infected individuals. Here we report that HIV-1 immunotherapy with a single injection of 3BNC117 impacts host antibody responses in viremic subjects. In comparison to untreated controls that showed little change in their neutralizing activity over a six-month period, 3BNC117 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
256
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(273 citation statements)
references
References 52 publications
6
256
0
4
Order By: Relevance
“…Whether individuals who have developed bnAbs exhibit a reduced susceptibility to HIV‐1 super‐infection has not been addressed, although as bnAbs constitute only part of the overall HIV‐specific antibody response they may not reach sufficient titers to do so. The lack of clinical impact of bnAbs is consistent with early bnAb infusion studies in animal models68 and humans69 that did not show a lasting impact on HIV‐1 viral loads, although newer, more potent bnAbs appear to have a more persistent impact on viral load70, 71, 72 and subsequent antibody development 73. At this time, ongoing clinical trials are being conducted to determine if bnAb infusion can augment other anti‐HIV‐1 therapies.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 62%
“…Whether individuals who have developed bnAbs exhibit a reduced susceptibility to HIV‐1 super‐infection has not been addressed, although as bnAbs constitute only part of the overall HIV‐specific antibody response they may not reach sufficient titers to do so. The lack of clinical impact of bnAbs is consistent with early bnAb infusion studies in animal models68 and humans69 that did not show a lasting impact on HIV‐1 viral loads, although newer, more potent bnAbs appear to have a more persistent impact on viral load70, 71, 72 and subsequent antibody development 73. At this time, ongoing clinical trials are being conducted to determine if bnAb infusion can augment other anti‐HIV‐1 therapies.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 62%
“…Most studies with anti-HIV monoclonal antibodies (MAbs) have examined the neutralization of cell-free virus (1)(2)(3)(4) or the prevention of intercel-lular transmission (5). In reality, MAbs likely exert anti-HIV effects in multiple ways, including by prevention of cellular infection; targeting of infected cells, including FcR-positive cells or complement, for destruction by Fc-mediated effects (6)(7)(8)(9); or delivery of a toxic payload to cells in the form of immunoconjugates (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). It is often assumed that the same MAbs that prevent the transmission of infection are also the most effective in eliminating persistently infected cells (21,22), despite evidence to the contrary (6,13,16,19).…”
Section: Importancementioning
confidence: 99%
“…Purging may be accomplished by the viral cytopathic effect, by established host defenses, or by actively eliminating cells with passively administered MAbs or cytotoxic immunoconjugates (17,20). MAbs may eliminate cells via Fc-mediated mechanisms (8,9), or they may be used in immunoconjugates that kill cells by the delivery of a toxin, small drug, or high-energy radioisotope. We and others have designed ITs targeted to cells expressing HIV Env (10,11,(13)(14)(15)(16)(17)(18)(19)(20)67).…”
Section: Efficacy Of Its Tested On Cells Transfected To Express Cell mentioning
confidence: 99%
“…It has been suggested that MAb administration can boost autologous adaptive immune responses (23,24), presumably by improved antibody-bound antigen delivery to and presentation by DC (22). We therefore measured humoral responses to HIV-1 Env in animals' day 0 and week 22 sera, a time point where N6-LS and PGT121 had been long cleared, against a panel of tier 1 (n ϭ 3) and tier 2 (n ϭ 4) HIV-1 pseudoviruses and the SHIV-SF162P3 challenge stock.…”
Section: Figmentioning
confidence: 99%